Analisis Pengaruh Arah Angin terhadap Gaya Dorong dan Tekanan pada Panel Surya Ground-Mounted - Zulfakar, Muhamad (Jurnal Informasi, Sains dan Teknologi, 2025)
Ground-mounted solar panels are directly exposed to environmental conditions, particularly wind, making structural design essential. While wind tunnel experiments have been a primary research method, they are costly and time-consuming. Computational Fluid Dynamics (CFD) simulations provide an efficient alternative by accurately modeling fluid-structure interactions, allowing for detailed aerodynamic analysis without physical testing. This study examines a solar panel configuration of 2×18 (1700×1200 mm panels) under a wind speed of 30 m/s at a height of 10 m. Wind direction variations (0°, 30°, 60°, 90°, 120°, 150°, 180°) significantly impact aerodynamic behavior. Drag Force analysis reveals that frontal wind (0°) generates the highest drag, while lateral wind (90°) has the least effect. Surface Pressure and Surface Coefficient (Cp) analysis indicate maximum pressure at 0°, where Cp values are highest, highlighting a pronounced pressure differential. At 90°, pressure distribution is more uniform, reducing aerodynamic impact. At 180°, rear-side pressure remains influential but lower than frontal exposure.